The Effect of the Problem-Based Learning (PBL) Instructional Model on the Cognitive Learning Outcomes of Grade X Students at MA Miftahul Ulum Bettet on the Topic of Environmental Pollution - Juwairiyah Juwairiyah; Moch Haikal (PAIDAGOGIA: Jurnal Inovasi Pendidikan dan Pembelajaran, 2025)
This study aimed to analyze the effect of the Problem-Based Learning (PBL) model on students' cognitive learning outcomes on the topic of environmental pollution in Grade X at MA Miftahul Ulum Bettet, Pamekasan. The study used a quantitative approach with a quasi-experimental, nonequivalent pretest–posttest control-group design. The sample consisted of two classes: X IPA C, the experimental class receiving PBL, and X IPA B, the control class receiving conventional instruction (lecture and discussion), totaling 47 students. Cognitive learning outcomes data were collected using a 9-item essay test measuring cognitive domains C1–C5, administered as both a pretest and posttest. Data were analyzed using the nonparametric Kruskal–Wallis test because the normality assumption was not met. The results showed a significant difference between the cognitive learning outcomes of students in the experimental and control classes, with posttest means of M = 66.8 (SD = 5.24) and M = 53.2 (SD = 4.81), respectively, and χ²(1) = 32.7; p < 0.001; ε² = 0.711, indicating a large effect. These findings indicate that implementing PBL is effective in improving students' cognitive learning outcomes in environmental pollution material and underscore its relevance as an alternative instructional model for developing critical thinking and problem-solving skills in Biology learning at the madrasah aliyah level.